2021
DOI: 10.1111/tra.12825
|View full text |Cite
|
Sign up to set email alerts
|

Hepatitis C virus core protein uses triacylglycerols to fold onto the endoplasmic reticulum membrane

Abstract: Lipid droplets (LDs) are involved in viral infections, but exactly how remains unclear.Here, we study the hepatitis C virus (HCV) whose core capsid protein binds to LDs but is also involved in the assembly of virions at the endoplasmic reticulum (ER) bilayer. We found that the amphipathic helix-containing domain of core, D2, senses triglycerides (TGs) rather than LDs per se. In the absence of LDs, D2 can bind to the ER membrane but only if TG molecules are present in the bilayer. Accordingly, the pharmacologic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 89 publications
0
9
0
Order By: Relevance
“…To best visualize PLIN3 recruitment to ER membranes, we generated intracellular giant ER vesicles (GERVs) by submitting cells to hypotonic medium [66, 71, 72] (Fig. 6A) .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…To best visualize PLIN3 recruitment to ER membranes, we generated intracellular giant ER vesicles (GERVs) by submitting cells to hypotonic medium [66, 71, 72] (Fig. 6A) .…”
Section: Resultsmentioning
confidence: 99%
“…The cells were then incubated at 37°C, 5% CO2 for 5 minutes, to induce GERVs, and then they were visualized. Neutral lipids’ synthesis was triggered by the addition of OA and Z-stacks imaging of different entire cells was performed before and 15 min after OA administration, as described in [72]. For the DGAT1 (Sigma, PF-04620110) and DGAT2 (Sigma, PF-06424439) inhibitors used in Cos7, the dilution applied was 1/1000 for a final concentration of 3ug/mL.…”
Section: Methodsmentioning
confidence: 99%
“…The infection of Huh7.5 cells by HCV (top right panel) induces the redistribution of AL to ER-derived remodeled membranes called membranous web (MW) ( 6 ), which is induced by HCV to achieve the viral replication, translation, and assembly within a protected environment. HCV core, probably through its high mobility on ER membranes ( 56 ), interacts with Nup98 from AL and translocates it within the MW and in close proximity of assembly sites, where it interacts with HCV RNA. In the absence of Nup98 (bottom left panel), the viral genome is excluded from the replication, assembly, and translation areas, leading to a decrease of infectious particle assembly.…”
Section: Discussionmentioning
confidence: 99%
“…The interaction between the D2 domain of core protein and LDs is critical for HCV assembly efficiency 93,94 . Ajjaji et al showed that the D2 domain of core protein resembles the ApoE lipid‐binding region and senses TAG in the bilayer membranes 95 . TAG in LDs facilitates the folding of core protein, which relocalizes to the contiguous ER regions, and blockage of TAG synthesis impedes HCV assembly 95 .…”
Section: Hepatitis C Virus (Hcv) and Ldsmentioning
confidence: 99%
“…Ajjaji et al showed that the D2 domain of core protein resembles the ApoE lipid‐binding region and senses TAG in the bilayer membranes 95 . TAG in LDs facilitates the folding of core protein, which relocalizes to the contiguous ER regions, and blockage of TAG synthesis impedes HCV assembly 95 . Two proline residues (P138 and P143) of core protein contribute to core‐LD interaction and core protein carrying P138A and P143A has no effect on LD morphology 96 .…”
Section: Hepatitis C Virus (Hcv) and Ldsmentioning
confidence: 99%